2016
DOI: 10.1093/toxsci/kfw046
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Lead Exposure Alters Gut Microbiota Composition and Results in Sex-specific Bodyweight Increases in Adult Mice

Abstract: Heavy metal pollution is a principle source of environmental contamination. Epidemiological and animal data suggest that early life lead (Pb) exposure results in critical effects on epigenetic gene regulation and child and adult weight trajectories. Using a mouse model of human-relevant exposure, we investigated the effects of perinatal Pb exposure on gut microbiota in adult mice, and the link between gut microbiota and bodyweight changes. Following Pb exposure during gestation and lactation via maternal drink… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(62 citation statements)
references
References 75 publications
4
54
1
2
Order By: Relevance
“…It is notable that both HMGA2 and FOXO are transcription factors that have been linked to metabolic‐related conditions. In a recent series of studies, which used the same longitudinal mouse cohort referenced in the current manuscript, we observed that perinatal Pb exposure leads to metabolic‐related physiological effects including increased food intake, body weight, body fat, activity changes, and insulin resistance in adult mice (Faulk et al, ; Wu et al, ). Although Pb toxicity research has traditionally focused on neurological‐related outcomes, other studies investigating developmental Pb exposure have also observed persistent physiological changes including decreased fetal and childhood growth in humans and late onset obesity in rodents (Gonzalez‐Cossio et al, ; Iavicoli et al, ; Leasure et al, ; Little et al, ; Afeiche et al, ).…”
Section: Discussionmentioning
confidence: 73%
“…It is notable that both HMGA2 and FOXO are transcription factors that have been linked to metabolic‐related conditions. In a recent series of studies, which used the same longitudinal mouse cohort referenced in the current manuscript, we observed that perinatal Pb exposure leads to metabolic‐related physiological effects including increased food intake, body weight, body fat, activity changes, and insulin resistance in adult mice (Faulk et al, ; Wu et al, ). Although Pb toxicity research has traditionally focused on neurological‐related outcomes, other studies investigating developmental Pb exposure have also observed persistent physiological changes including decreased fetal and childhood growth in humans and late onset obesity in rodents (Gonzalez‐Cossio et al, ; Iavicoli et al, ; Leasure et al, ; Little et al, ; Afeiche et al, ).…”
Section: Discussionmentioning
confidence: 73%
“…Further, the altered insulin response was non-monotonic in relation to exposure. Using the same cohort of mice, the gut microbiota was compared between control mice and the high Pb exposure group of 10-month-old mice, finding that perinatal Pb exposure induced changes in gut microbiota in adult male and female mice, but microbiota changes were correlated to increases in body weight in male mice only [48]. …”
Section: Periconceptional Exposures To Lead (Pb)mentioning
confidence: 99%
“…In addition, reduced aerobic bacteria and increased anaerobic bacteria were observed in the exposed offspring. Lastly, Pseudomonas, Enterobacter, and Desulfovibrio were found in higher abundances in exposed adult mice than in controls (p < 0.05) [43]. Ba et al (2017) [42] demonstrated the sex-specific effects of low-dose exposure to cadmium and found that early exposure to 100 nM induced fat accumulation in adult male C57BL/6J mice.…”
Section: Metalsmentioning
confidence: 90%
“…These changes in metabolite homeostasis are important risk factors involved in tissue dysfunctions, which may cause diseases such as obesity and diabetes [139]. [43] reported that perinatal lead (Pb) exposure (32 ppm) in the drinking water, in wild-type non-agouti (a/a) mice of the Avy strain isogenic mouse model of perinatal environmental exposure, induced changes in the adult offspring gut microbiota. These changes were sex-independent, but a strong association was found between male offspring and increased body weight.…”
Section: Metalsmentioning
confidence: 99%